2021
DOI: 10.3390/nu13082835
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Dietary Patterns and Their Associations with Overweight/Obesity among Chinese Adults: China Health and Nutrition Survey 1991–2018

Abstract: It is essential to understand the impact of different dietary pattern trajectories on health over time. Therefore, we aimed to explore the long-term trajectories of dietary patterns among Chinese adults and examine the prospective association between different trajectory groups and the risk of overweight/obesity. The sample was 9299 adults aged 18 years or older from the China Health and Nutrition Survey (CHNS) between 1991 and 2018. We used factor analysis to identify dietary patterns and group-based trajecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…This finding is contrary to the result of the current study. The heterogenous results may be attributed to the differential dietary habits between Japanese and Chinese adults [ 9 , 10 ], which may play an important role in altering Cu absorption and bioavailability [ 53 ]. These data require further investigation in larger prospective cohort studies, and exploration of the causal relationships between dietary Cu intake and T2DM risk and related risk factors in randomized controlled trials in China are also required to provide useful information for updating the DRIs of Cu [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is contrary to the result of the current study. The heterogenous results may be attributed to the differential dietary habits between Japanese and Chinese adults [ 9 , 10 ], which may play an important role in altering Cu absorption and bioavailability [ 53 ]. These data require further investigation in larger prospective cohort studies, and exploration of the causal relationships between dietary Cu intake and T2DM risk and related risk factors in randomized controlled trials in China are also required to provide useful information for updating the DRIs of Cu [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is only one cohort study in Japan that has reported a positive relationship between dietary Cu intake and T2DM risk [ 8 ]. As Japan has different dietary habits from China [ 9 , 10 ], whether the association between dietary Cu intake and the risk of T2DM in Japanese adults is identical to the association in Chinese adults is unclear. Therefore, it is necessary to explore the association between dietary Cu intake and the risk of T2DM in Chinese adults.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the wide range of healthy and detrimental dietary patterns worldwide provides valuable knowledge to prevent chronic diseases [65][66][67][68]. However, when designing nutritional interventions strategies containing healthy dietary components, these should be tailored to the population's genetic background, regional foods, and culinary culture [27,69].…”
Section: Discussionmentioning
confidence: 99%
“…According to estimates by the International Food and Agriculture Organization (FAO), the prevalence of undernutrition in China has decreased from 24% in the early 1990s to less than 10% in recent years [12]. On the other hand, due to the structural changes in diet, some highly processed foods that are high in fat and sugar have become overconsumed, and this has led to the occurrence of non-communicable diseases such as diabetes and overweight obesity [13,14]. To address the coexistence of undernutrition and overnutrition and to guide residents toward a healthy diet, the National Health and Family Planning Commission of the People's Republic of China (NHFPC) released the 2016 China Dietary Guidelines (CDG2016), which provide specific dietary recommendations for all healthy people over the age of two years in China.…”
Section: Introductionmentioning
confidence: 99%